Functional Characterization of c-di-GMP Signaling-Related Genes in the Probiotic Lactobacillus acidophilus - He, Jiahui; Ruan, Wenhao; Sun, Jieli; Wang, Fang; Yan, Wenjuan (Frontiers in Microbiology, 2018)
The bacterial second messenger cyclic diguanylate monophosphate (c-di-GMP) regulates a series of cellular functions, including biofilm formation, motility, virulence, and other processes. In this study, we confirmed the presence of several c-di-GMP related genes and evaluated their activities and functions in Lactobacillus species. Bioinformatic and biochemical analyses revealed that Lactobacillus acidophilus La-14 have an active c-di-GMP phosphodiesterase (PdeA) that may act in the metabolic cycle of c-di-GMP. A GGDEF protein (DgcA) induced two c-di-GMP-dependent phenotypes (low motility and high production of curli fimbriae) in Escherichia coli by heterologously expressed in vivo but showed no diguanylate cyclases activity in vitro while in the expression without the N-terminal transmembrane domain. The degenerated EAL-domain protein (PdeB), encoded by the last gene in the gts operon, serve as a c-di-GMP receptor which may be associated with exopolysaccharide (EPS) synthesis in L. acidophilus. Heterologously expressed GtsA and GtsB, encoded by the gts operon, stimulated EPS and biofilm formation in E. coli BL21. Constitutive expression in L. acidophilus revealed that a high concentration of intracellular DgcA levels increased EPS production in L. acidophilus and enhanced the co-aggregation ability with E. coli MG1655, which may be beneficial to the probiotic properties of Lactobacillus species. Our study imply that the c-di-GMP metabolism-related genes, in L. acidophilus, work jointly to regulate its functions in EPS formation and co-aggregation.